'Fire Burn and Cauldron Bubble': What are the Conjunctural Effects on English Teacher Professional Memories, Identities and Narratives?. Issue 1 (2nd January 2016) - Tarpey, Paul
Abstract: This article explores how circumstances in different conjunctures influence the types of narrative, working practice and 'Professional Memory' that English teachers construct. It is argued that the circumstances in which teachers begin their careers help to formulate attitudes, values and missions that remain potent over long periods. Examining these phenomena from a collectivist perspective makes it possible to uncover the valued ways of working and conceptions of 'English' that different generations hold through professional memory. These memories can provide much needed, alternative accounts of the subject that are both informative and instructive. Here, I concentrate on the professional memory of one generation of English teachers who began in a distinctive conjuncture: 1965–1975.